‘I was ‘only’ seen as a birthing woman:’ the pregnancy, birth and postpartum experiences of women with refugee backgrounds in Norway - Hilde Sjobo Asbjornsen; Fungisai Gwanzura Ottemöller; Eline Skirnisdottir Vik (BMC Pregnancy and Childbirth)
Abstract Background Norway is recognised for its high-quality maternal healthcare. However, health equity has yet to be achieved. This study explored the experiences of women with refugee backgrounds during pregnancy, birth, and postpartum in Norway. We aimed to understand how the diversity of their backgrounds and current life circumstances, influenced the women’s health, well-being, and interactions with maternal healthcare services. The study focused on the perspectives of women whose needs have not been fully acknowledged in maternal healthcare services both at national and local levels. Method Consistent with our Feminist Participatory Action Research approach, we included multicultural doulas, women with lived experience of migration and giving birth in Norway, as co-researchers. We also collaborated with practitioners such as midwives and other relevant actors. We recruited and conducted qualitative interviews with ten women with refugee backgrounds who had given birth in Norway. Results Our findings revealed that the women’s intersecting identities were crucial in shaping their maternal healthcare needs during pregnancy, birth and postpartum. The structural inequities faced in maternal healthcare services during pregnancy such as lack of language and communication support, limited access to social support networks, and unfamiliarity with healthcare services were also apparent during birth and postpartum. Adjusting to a new country while raising children compounded these challenges, impacting experiences of pregnancy, birth, and postpartum. Conclusion This study highlights the importance of adopting an intersectional approach to maternal healthcare, and not treating race, class, gender and migration experiences in isolation, but taking them into consideration when designing and implementing services. Our results suggest that current policies and services often overlook the specific needs of women with refugee backgrounds. To achieve true health equity in maternal healthcare services, policies should prioritize these women’s unique needs and experiences, ensure that services are adapted and properly funded, and that initiatives guarantee active participation and representation from women with refugee backgrounds.